Desjudicialização da execução civil - comentários ao projeto de lei n. 6.204/2019 - Rocha, Silvania (2024)
This work intends to study the immediate need to de-judicialize civil execution (to pay an amount), with the displacement of the administrative activity of the procedure, through delegation, from the Judiciary to an enforcement agent (protest notary, for example), aiming to reduce the procedural crisis created due to high procedural demands. It is important to highlight that, even with the shift of the activity from the judge to the notary, the constitutional principles of due legal process, adversarial proceedings, broad defense, double degree of jurisdiction will always be observed, with the Judiciary, including the CNJ, as a backdrop, ensuring the application of justice. The work was mainly based on bibliographical review, analysis of statistical data and field research carried out in civil court forums in the District of the Capital of São Paulo. Conclusively, it can be said that dejudicialization is one of the measures to be adopted to contain the high procedural demands, as it is a technique compatible with the constitutional provision and that the displacement of this administrative activity from the execution of the judge to the notary can, greatly contribute to solving the issue of credit in Brazil, over-indebtedness, the effectiveness of judicial decisions, and strengthening confidence in the Judiciary as the guardian of justice.